2004
DOI: 10.1097/01.jcp.0000130555.63254.73
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-site Dose Ranging Study of Nalmefene in the Treatment of Alcohol Dependence

Abstract: The opiate antagonist nalmefene has been shown in 2 single-site studies to reduce alcohol consumption and relapse drinking in alcohol-dependent individuals. This safety and preliminary multisite efficacy study evaluated 3 doses of nalmefene (5, 20, or 40 mg) in a double-blind comparison to placebo over a 12-week treatment period in 270 recently abstinent outpatient alcohol-dependent individuals. Participants concomitantly received 4 sessions of a motivational enhancement therapy (with a medication compliance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 38 publications
1
55
1
7
Order By: Relevance
“…While studies of the treatment of alcoholism using nalmefene have been mixed (Mason et al, 1994;Anton et al, 2004), initial studies of nalmefene in the treatment of compulsive gambling have been promising (SW Kim, personal communication). Naltrexone and nalmefene do have comparable affinity at mu-and kappa-opioid receptors.…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies of the treatment of alcoholism using nalmefene have been mixed (Mason et al, 1994;Anton et al, 2004), initial studies of nalmefene in the treatment of compulsive gambling have been promising (SW Kim, personal communication). Naltrexone and nalmefene do have comparable affinity at mu-and kappa-opioid receptors.…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
“…Naltrexone's effectiveness is poor for the former and moderate for the latter (San et al, 1991;Volpicelli et al, 1992;O'Malley et al, 1992O'Malley et al, , 2002. Nalmefene also has a moderate treatment effect for alcoholism but is not yet available for this indication (Mason et al, 1994;Anton et al, 2004). Naloxone, naltrexone, and nalmefene are moderately selective ligands for the three opioid receptor subtypes (mu, kappa, and delta).…”
Section: Introductionmentioning
confidence: 99%
“…Naltrexone is now an approved drug for the treatment of alcoholism based on its efficacy in reducing craving for and consumption of ethanol (Volpicelli et al, 1992), and nalmefene has shown clinical utility in the treatment of alcoholism (Mason et al, 1994;Anton et al, 2004). However, naltrexone, although classified as a general opioid receptor antagonist, actually has a higher affinity for the m-opioid receptor subtype than the d and k subtypes at low doses (Abbott et al, 1986;Millan, 1989;Millan et al, 1989;Walker et al, 1994;Stromberg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This found two adverse events reported significantly more frequently by patients on Anton et al [127] compared 5mg, 20mg and 40mg nalmefene with placebo, and Mason et al [125] 20mg and 80mg doses of nalmefene with placebo. Patients on 80mg nalmefene were more likely to withdraw due to adverse effects but the occurrence of adverse drug reactions did not significantly differ between the groups.…”
Section: Pharmacokinetic Considerations and Implications For Safetymentioning
confidence: 79%